2009
DOI: 10.1073/pnas.0900666106
|View full text |Cite
|
Sign up to set email alerts
|

A P-type ATPase importer that discriminates between essential and toxic transition metals

Abstract: Transition metals, although being essential cofactors in many physiological processes, are toxic at elevated concentrations. Among the membrane-embedded transport proteins that maintain appropriate intracellular levels of transition metals are ATP-driven pumps belonging to the P-type ATPase superfamily. These metal transporters may be differentiated according to their substrate specificities, where the majority of pumps can extrude either silver and copper or zinc, cadmium, and lead. In the present report, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 32 publications
3
74
0
2
Order By: Relevance
“…In Pseudomonas aeruginosa, which possesses two operons encoding cbb 3 and a homologue of ctpA (PA1549), the PA1549 mutant did not show any phenotype in excess copper (27). More recently, expression of ctpA (PA1549) in the copper-sensitive strain of E. coli (GG44) did not restore resistance to copper (28). Similar results were previously obtained in R. capsulatus; the ccoI Ϫ mutant was neither resistant nor hypersensitive to exogenous copper (8).…”
Section: Discussionsupporting
confidence: 73%
“…In Pseudomonas aeruginosa, which possesses two operons encoding cbb 3 and a homologue of ctpA (PA1549), the PA1549 mutant did not show any phenotype in excess copper (27). More recently, expression of ctpA (PA1549) in the copper-sensitive strain of E. coli (GG44) did not restore resistance to copper (28). Similar results were previously obtained in R. capsulatus; the ccoI Ϫ mutant was neither resistant nor hypersensitive to exogenous copper (8).…”
Section: Discussionsupporting
confidence: 73%
“…In contrast with many P IB -ATPases (Rensing et al, 2000;Lewinson et al, 2009), both S. solfataricus ATPases were incapable of compensating for the copper transport defect of the E. coli copA mutant. The small increase in growth rate at elevated temperatures may indicate weakly developing complemention.…”
Section: Expression Of Copa and Copbmentioning
confidence: 86%
“…2, because both ATPases of S. solfataricus belong to the other subgroup CopA-1, which comprises ATPases in charge of copper homeostasis. CopA-1-type ATPases are assigned as resistance factors exporting copper at high rates (Argüello et al, 2007;Osman & Cavet, 2008), whereas a few ATPases have been previously considered to be copper importers due to their phenotypic characteristics (Odermatt et al, 1993;Tottey et al, 2001;Lewinson et al, 2009). These apparently conflicting views have been lately reconciled by the statement that ''all Cu + -ATPases drive cytoplasmic Cu + -efflux, albeit at quite different transport rates'' .…”
Section: Phylogenetic Relationship Of Copa and Copbmentioning
confidence: 99%
See 1 more Smart Citation
“…They explained the mutant phenotype by the possibility of defects in copper uptake [26]. Furthermore, Lewinson et al [27] reported a copper-importing P-type ATPase, HmtA (heavy metal transporter A), in P. aeruginosa Q9I147 and confirmed their claim by many in vivo assays including, intracellular metal measurements. These results supported the proposal that Mc.…”
Section: ) Bioinformatic Analyses and Protein Topology Of Copa Protementioning
confidence: 95%